Design and Implementation of a Biologically Inspired Swimming Robot - An EPS@ISEP 2014 Spring Project - Ishii, Alicia Moreno (2015)
This paper presents the development of a fish-like robot called Bro-Fish. Bro-Fish aims to be an educational toy dedicated to teaching mechanics, programming and the physics of floating objects to youngsters. The underlying intention is to awaken the interest of children for technology, especially biomimetic (biologically inspired) approaches, in order to promote sustainability and raise the level of ecological awareness. The main focus of this project was to create a robot with carangiform locomotion and controllable swimming, providing the opportunity to customize parts and experiment with the physics of floating objects. Therefore, the locomotion principles of fishes and mechanisms developed in related projects were analysed. Inspired by this background knowledge, a prototype was designed and implemented. The main achievement is the new tail mechanism that propels the robot. The tail resembles the undulation motion of fish bodies and is actuated in an innovative way, triggered by an elegant movement of a rotating helicoidal. First experimental tests revealed the potential of the proposed methodology to effectively generate forward propulsion.